2015
DOI: 10.18632/oncotarget.4406
|View full text |Cite
|
Sign up to set email alerts
|

ALDH1A1-overexpressing cells are differentiated cells but not cancer stem or progenitor cells in human hepatocellular carcinoma

Abstract: Aldehyde dehydrogenase 1A1 (ALDH1A1) is considered to be a cancer stem cell marker in several human malignancies. However, the role of ALDH1A1 in hepatocellular carcinoma (HCC) has not been well elucidated. In this study, we investigated the relationship between ALDH1A1 and clinicopathological findings and examined whether ALDH1A1 deserves to be a cancer stem cell marker in HCC. Sixty HCC samples obtained from surgical resection were collected for immunohistochemical (IHC) staining. Of these 60 samples, 47 sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 36 publications
2
31
1
Order By: Relevance
“…were not colocalized with ALDH1-expressing cells in HCC [100]. Consequently, immunohistochemistry with an ALDH1 antibody shows diferentiated cells that look like mature hepatocytes but not CSCs.…”
Section: Aldh1 In Hccmentioning
confidence: 84%
See 2 more Smart Citations
“…were not colocalized with ALDH1-expressing cells in HCC [100]. Consequently, immunohistochemistry with an ALDH1 antibody shows diferentiated cells that look like mature hepatocytes but not CSCs.…”
Section: Aldh1 In Hccmentioning
confidence: 84%
“…ALDH1 expression evaluated by immunohistochemistry is heterogenous and is present in the normal liver tissue, especially in hepatocytes [100]. However, ALDH bright cells, including ALDH1 isoforms, evaluated using the Aldeluor assay, have been reported to be a marker of liver progenitor cells in the normal liver tissue [101] and of CSCs in HCC [102].…”
Section: Aldh1 In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…Aldehyde dehydrogenase 1A1 is an intracellular enzyme that is widely expressed in adult organs, such as the liver, kidney, brain, and lungs. It oxidizes retinaldehyde to retinoic acid, and thereby regulates a variety of biological processes, such as cell proliferation, differentiation, and apoptosis . Previous studies have shown that ALDH1A1 expression is associated with tumor progression and poor prognosis in several cancers, including lung, gastric, ovarian, and breast cancers .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, IHC has several advantages over IF technique including: 1) capability of being repeatedly used in order to search for few positive cells, 2) no reduction in signal intensity, 3) provides superior morphological information, and 4) could be utilized to distinguish between normal and cancerous tissue. Therefore, in cancerous tissues, double-staining IHC is practically suitable for observing stem cell and CSC markers [3,4]. CSCs are a rare subpopulation of tumor cells thought to be responsible for cancer initiation, maintenance, growth, metastasis, recurrence, and resistance to treatments [5].…”
Section: Introductionmentioning
confidence: 99%